Letter: inconsistency in reporting of hypophosphatemia after intravenous iron. Issue 6 (14th August 2017) - Schaefer, B.; Glodny, B.; Wolf, M.; Zoller, H.
Abstract : Linked Content This article is linked to Aksan et al papers. To view these articles visithttps://doi.org/10.1111/apt.14043 andhttps://doi.org/10.1111/apt.14254 .